On improved class of difference type estimators for population median in survey sampling. Issue 10 (19th May 2022) - Shabbir, Javid; Gupta, Sat; Narjis, Ghulam
Abstract: We propose two new improved class of difference type estimators for population median under simple random sampling (SRS) and two-phase sampling (TPS). Expressions for bias and MSE are derived up to first order of approximation. We make a comparison of proposed estimators with all other commonly known estimators in literature. Numerical findings show that the proposed class of estimators perform better as compared to all other estimators considered here.